PENGUATAN KELEMBAGAAN BANK SAMPAH MELALUI EDUKASI LINGKUNGAN DAN DIGITALISASI SISTEM PENCATATAN DI DESA BETITING GRESIK - Alvy Mulyaning Tyas; Sri Utami Ady; Shanty Ratna Damayanti; Jajuk Suprijati; Achmad Choiron (Jurnal Terapan Abdimas, 2026)
Abstract. The issue of household waste management remains a major challenge in rural areas. Low community participation and manual administrative systems have caused the activities of the Waste Bank Unit (BSU) in RW 05, Betiting Village, to run suboptimally. This community service program aims to strengthen the capacity of BSU administrators in conducting outreach, increasing community participation, and implementing a digital recording system to create transparent and sustainable waste management. The implementation methods included training on effective communication, developing environmental education media, and providing training on the use of Google Forms and Google Sheets for digital record-keeping. The program was attended by 20 waste bank administrators. The evaluation results showed a 32% increase in administrators knowledge and understanding of effective communication, measured through pre-test and post-test assessments. In addition, 100% of participants were able to implement the digital recording system for waste weighing and reporting activities. The adoption of this digital system improved administrative accuracy and supported transparency in waste management practices at the Waste Bank Units in RW 05, Betiting Village, Cerme District.Abstrak. Permasalahan pengelolaan sampah rumah tangga masih menjadi tantangan utama di wilayah pedesaan. Rendahnya partisipasi warga dan sistem administrasi manual menyebabkan kegiatan Bank Sampah Unit (BSU) RW 05 Desa Betiting belum berjalan optimal. Kegiatan pengabdian ini bertujuan untuk meningkatkan kapasitas pengurus dalam sosialisasi, memperkuat partisipasi masyarakat, serta menerapkan sistem pencatatan digital guna menciptakan pengelolaan sampah yang transparan dan berkelanjutan. Metode pelaksanaan meliputi pelatihan komunikasi efektif, pembuatan media edukasi lingkungan, serta pelatihan penggunaan Google Form dan Google Sheets untuk digitalisasi pencatatan. Kegiatan ini diikuti oleh 20 orang pengurus BSU RW 05. Hasil evaluasi menunjukkan adanya peningkatan tingkat pengetahuan dan pemahaman pengurus terkait komunikasi efektif sebesar 32%, yang diukur melalui perbandingan nilai pre-test dan post-test. Selain itu, 100% pengurus telah mampu mengimplementasikan sistem pencatatan digital dalam proses penimbangan dan pelaporan sampah. Penerapan sistem ini meningkatkan kerapian administrasi serta mendukung transparansi pengelolaan Bank Sampah Unit di lingkungan RW 05 Desa Betiting Kecamatan Cerme.